The Factors Affecting E-Banking Service Satisfaction and Usage Behavior - Sidra Sidra; Shah Mehmood Wagan (TIJAB (The International Journal of Applied Business), 2025)
Background: The study focuses on the use and satisfaction of e-banking in China, highlighting the importance of customer satisfaction. Objective: This study aims to determine customer satisfaction, the most used features, determinants of e-banking use, characteristics of websites, and user satisfaction levels. Method: The study combines the Technology Acceptance Model (TAM), Theory of Planned Behavior (TPB), and Expectation Confirmation Theory (ECT) to assess key variables such as user attitude, ease of use, usefulness, perceived value, trust, service quality, and satisfaction with e-banking services through questionnaire surveys and Smart PLS 4 data analysis tools. Results: The study found that perceived value, trust, and service quality are the main determinants of satisfaction, while perceived usefulness and ease of use significantly affect user attitudes. In addition, although security risks have a non-significant impact on attitudes, performance risks still have a negative impact. Conclusion: The study also pointed out that young people are the main user group of e-banking services, and banks need to improve service quality to meet user needs and enhance user satisfaction. Overall, e-banking services have advantages in improving convenience and reducing costs, but they need to continuously optimize user experience to expand market share. Keywords: E-banking; Attitude; Trust; Risk Performance; Satisfaction